THE PORTRAYAL OF ANDROGYNOUS SOCIETY IN THE LEFT HAND OF DARKNESS BY URSULA K. LE GUIN - Efendi, Ridwan (2015)
The present study entitled The Portrayal of Androgynous Society in The Left Hand of Darkness by Ursula K. Le Guin attempts to analyze the construction of androgyny through the major androgynous characters. The study was conducted in order to explore the concept of gender identity which was portrayed in the novel. Gender criticism approach proposed by Bressler (2007) was used as the theoretical framework which aimed at investigating gender in the production of literature. The study found that there were two types of androgynous characters which were rooted from the traditional gender-based orientation: masculinized and femininized androgynous. There was an indication that those types of construction destabilized the concept of androgyny. Thus, the novel failed to portray the characters who were supposed to have no tendency towards any traditional gender identities. Keywords: gender criticism, gender identity, portrayal, androgynous Penelitian berjudul The Portrayal of Androgynous Society in The Left Hand of Darkness by Ursula K. Le Guin berupaya untuk menganalisa konstruksi androgini melalui tokoh-tokoh androgini utama. Tujuan dari penelitian ini adalah untuk menelusuri konsep identitas gender yang tergambar di dalam novel. Pendekatan gender criticism yang dikemukakan oleh Bressler (2007) digunakan sebagai landasan teori yang bertujuan untuk menyelidiki gender dalam produksi karya sastra. Penelitian menemukan dua tipe tokoh androgini yang berakar dari orientasi gender tradisional: masculinized dan femininized androgynous. Terdapat indikasi bahwa dua jenis karakter androgini tersebut telah membuat konsep yang tidak stabil. Maka dari itu, novel ini telah gagal dalam menggambarkan tokoh-tokoh yang seharusnya tidak memiliki kecenderungan terhadap identitas gender tradisional. Kata kunci: gender criticism, identitas gender, penggambaran, androgini